2006
DOI: 10.2307/4134604
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Genetic Variation Indicate Cryptic Species Within Lamarck’s Little Sea Star,Parvulastra(=Patiriella)exigua

Abstract: The asterinid sea star Parvulastra exigua (Lamarck) is a common member of temperate intertidal marine communities from geographically widespread sites around the southern hemisphere. Individuals from Australian populations lay benthic egg masses (through orally directed gonopores) from which nonplanktonic offspring hatch and metamorphose without a dispersing planktonic larval phase. Scattered reports in the taxonomic literature refer to a similar form in southern Africa with aborally directed gonopores (and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 39 publications
0
32
0
Order By: Relevance
“…In the understudied Indo-Pacific, numerous cryptic species have been described including fishes (Colborn et al 2001, Messmer et al 2005, Hubert et al 2012, sponges (Muricy 2011), several groups of crustaceans Boyce 2006, Poore and, molluscs (Bouchet et al 2002, Pola et al 2012, echinoderms (Landry et al 2003, Hart et al 2006, Uthicke et al 2010, and jellyfishes Martin 2001, Holland et al 2004). Uncovering cryptic species, either as sibling species or as species flocks, allows rare insights into the processes driving speciation in marine environments, especially where species cooccur without evidence of strong vicariant barriers .…”
Section: Species Identificationmentioning
confidence: 99%
“…In the understudied Indo-Pacific, numerous cryptic species have been described including fishes (Colborn et al 2001, Messmer et al 2005, Hubert et al 2012, sponges (Muricy 2011), several groups of crustaceans Boyce 2006, Poore and, molluscs (Bouchet et al 2002, Pola et al 2012, echinoderms (Landry et al 2003, Hart et al 2006, Uthicke et al 2010, and jellyfishes Martin 2001, Holland et al 2004). Uncovering cryptic species, either as sibling species or as species flocks, allows rare insights into the processes driving speciation in marine environments, especially where species cooccur without evidence of strong vicariant barriers .…”
Section: Species Identificationmentioning
confidence: 99%
“…The answer has often been based on subjective and taxon-specific experience or patterns. Several recent studies (Wiens & Penkrot 2002;Morando et al 2003;Cardoso & Vogler 2005;Hart et al 2006;Monaghan et al 2006;Pons et al 2006) have shown in specific contexts that there can be a simple correspondence between the identity of traditional species or ESUs and an objective standard of genetic differentiation: the 95% connection limit in statistical parsimony networks (Posada & Crandall 2001;Templeton 2001). Here we show in a literature survey and a reanalysis of two barcoding studies that this operational species definition appears to be general and quantitatively reliable across a broad range of taxa and genetic markers.…”
Section: Introductionmentioning
confidence: 99%
“…P. exigua is a prominent member of intertidal marine communities where it is an important grazer on microalgae (Arrontes and Underwood 1991;Jackson et al 2009). Based on phylogenetic data, only one mitochondrial lineage of P. exigua is present in Australia indicating the presence of a single species in this region (Waters and Roy 2004;Hart et al 2006). The cryptic 'pseudoexigua' morphospecies complex in tropical Australia (and elsewhere) was allocated to a new genus (Cryptasterina) and P. exigua sensu stricta was clarified (Dartnall et al 2003).…”
Section: Introductionmentioning
confidence: 98%
“…The cryptic 'pseudoexigua' morphospecies complex in tropical Australia (and elsewhere) was allocated to a new genus (Cryptasterina) and P. exigua sensu stricta was clarified (Dartnall et al 2003). Some isolated Southern Ocean island populations of P. exigua may include cryptic species (Hart et al 2006).…”
Section: Introductionmentioning
confidence: 99%